QE3 and Asia : concerns over new monetary easings - J. Soedradjad Djiwandono (2012)
Quantitative easing in different forms have recently been resorted to by the US Federal Reserve (Fedres), the European Central Bank (ECB) and the Bank of Japan (BoJ) to rescue their respective economies from prolonged recession. Are these efforts effective? What are the implications for Asia’s emerging economies?